System development and assessment for green hydrogen generation and blending with natural gas - Ozturk, Merve; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
In this study, an integrated system is designed and studied to produce renewable (green) hydrogen and blend it with natural gas potentially available in the Black Sea for countrywide utilization, and a case study is, in this regard, considered for the city of Zonguldak in Turkey. To utilize the natural gas reserves in a more environ-mentally friendly and efficient manner, blending it with the addition of 20% hydrogen by volume is the prime focus of this study. For this purpose, hydrogen production capacities from renewable sources of energy, namely wind, solar and wave, are calculated and found out as 1432 kg, 174,210 kg, and 1257 kg, respectively. The effects of hydrogen content addition on the blend gas consumption and the lifetime of proven reserves are investigated. With the addition of 20% hydrogen by volume, the annual blend gas consumption increases from 46.55 billion cubic meters (Bm3) to 54.11 Bm(3), while the consumption of natural gas decreases from 46.55 Bm(3 )to 43.29 Bm3. Thus, the life span increases from 11.6 years to 12.5 years, respectively. The CO and CO2 emissions potentially released after the combustion decrease from 0.05 g/day and 32% to 0.02 g/day and 28% when the hydrogen content in the blend increases from 5% to 20%, accordingly. Furthermore, NOx emissions increase from 4.08 g/day to 7.54 g/day in the exhaust gas when the hydrogen addition is changed from 5% to 20% in the blend.
Keywords: Energy; Hydrogen; Natural gas; Solar energy; Wave energy; Wind energy; Environment; Sustainability; POWER; Thermodynamics; Energy & Fuels